Effectivity of using rice husk ash and fly ash as stabilizer in reducing the swelling of smectite-type of clays - Picar, Cyril Jerlo B.; Yanos, Frances Marie G.; Antonio, Oscar Victor M. Jr. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Bentonite clay is a member of the smectite-group of clays. In places where there are large seasonal variations such as the Philippines, structures and roadways built on expansive soils such as the smectite-type clay are subjected to periodic swelling and shrinkage cycles which results to undesirable cracking and fatigue in the structures. With this regard, this study focuses on the use of Fly Ash and Rice Husk Ash as stabilizers in reducing the swelling of these smectite-type of clays. The different geotechnical properties of the soil were observed with the addition of different concentration of rice husk ash and fly ash with a constant concentration of lime. The geotechnical properties observed include: Liquid Limit, Plastic Limit, Activity Index, Free Swell Index, Maximum Dry Density and Optimum Moisture Content, and Unconfined Compressive Strength. All the experimental methods and all laboratory procedures that were used in this study except for the Free Swell Index were conducted in accordance with the American Society tor Testing and Materials (ASTM) standards. The Free Swell Index was conducted in accordance with the Indian Standard (IS) 2770. After the series of experiments, it was found out that indeed, the use of fly ash is effective in reducing the swelling of bentonite clays and is an effective stabilizer because of the increase in compressive strength. Since bentonite have high activity index, the use of fly ash was concluded to be effective in all types of expansive soils. On the other hand, the use of rice husk ash was found out to be not as effective. Although the use of rice husk ash reduces the expansion of the soil, the strength was significantly compromised.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Rice hull ash; Fly ash; Soil conditioners; Soil stabilization